Lineage isolation in the face of active gene flow in the coastal plant wild radish is reinforced by differentiated vernalisation responses. Issue 1 (December 2016) - Han, Qingxiang; Higashi, Hiroyuki; Mitsui, Yuki; Setoguchi, Hiroaki
Abstract Background The respective role and relative importance of natural selection and gene flow in the process of population divergence has been a central theme in the speciation literature. A previous study presented conclusive evidence that wild radish on Japanese islands comprises two genetically isolated lineages: the southern and northern groups. However, a general understanding of the lineage isolation with frequent seed flow of the coastal plant species is still unclear. We surveyed nucleotide polymorphisms over 14 nuclear loci in 72 individuals across the Japan–Ryukyu Islands Arc to address the demographic history of wild radish utilising the isolation-with-migration (IM) model. In addition, we investigated the flowering times of individuals in different wild radish lineages, with and without cold exposure, to assess their respective vernalisation responses. Results Coalescent simulations suggested that divergence between the southern and northern lineages of wild radish began ~18, 000 years ago, initially during the Last Glacial Maximum (LGM) period. The gene flow from the southern to northern groups was considerably higher than that in the opposite direction, indicating effective dispersal of viable seeds via the northward Kuroshio Current. Our greenhouse experiments indicated that cold exposure was not required for flowering in the southern group, but could advance the date of flowering, suggesting that vernalisation would be facultative in the southern group. In contrast, the northern group was either unable to flower or flowered later without prior cold exposure, and thus had an obligate requirement for cold treatment. Conclusions The south–north lineage divergence in wild radish could be triggered by a directional change in the sea current during the ice age, despite gene flow due to the high dispersability and longevity of seeds. We also found that temperature profoundly affected the vernalisation responses of wild radish, which may repress reproductive success and ultimately drive and reinforce intra-specific differentiation between the two lineages of wild radish. This study provides new insights into the maintenance of lineage differentiation with on-going gene flow in coastal plants.